Titanium Vacancies in TiO2 Nanofibers Enable Highly Efficient Photodriven Seawater Splitting - Zhang, Yan‐Xiang; Wu, Si‐Ming; Tian, Ge; Zhao, Xiao‐Fang; Wang, Li‐Ying; Yin, Yi‐Xia; Wu, Lu; Li, Qian‐Ni; Zhang, Yue‐Xing; Wu, Jin‐Song; Janiak, Christoph; Ozoemena, Kenneth I.; et al. (Chemistry : a European journal, 2021)
Invited for the cover of this issue are Xiao‐Yu Yang and co‐workers at Wuhan University of Technology, Heinrich‐Heine‐Universität Düsseldorf, University of the Witwatersrand, and Ben‐Gurion University of the Negev. The image depicts Ti vacancies in TiO2 as powerful drivers of photo‐ and photo‐electrocatalytic seawater splitting for hydrogen production. Read the full text of the article at 10.1002/chem.202101817. “We think this can provide new insight into the design of high‐performance catalysts for seawater splitting.” Read more about the story behind the cover in the Cover Profile and about the research itself on page 14202 ff. (DOI: 10.1002/chem.202101817).